Human Resources Management Practices and Graduate Employability from the Perspectives of Management - Mokhtar, Norsyahida; Abu Seman, Noor Aslinda; Jusoh, Nur Aniza Quantaniah (Research in Management of Technology and Business, 2021)
The skills mismatches between recent graduates and employers’ demands are the main driver of graduate unemployment. The purpose of this empirical study is to understand the current trends of human resource development strategies, attributes and developmental program required by employees regarding employability when hiring entry-level graduates. A total of 12 respondents from management staff of private engineering company in Ayer Hitam, Johor were involved in face-to-face interview as qualitative approach medium. This study used thematic analysis as data analysis. The findings found the working experience is the main factors in hiring employee. The result also found ICT exposure and knowledge, problem-solving thinking and team work were major attributes required for graduate employment. It also found training and development program and financial and non-financial opportunity were major developmental activities provided by company to support graduate employability. Therefore, this study may assist the employers as guidance regarding graduate employability strategy development in hiring and developmental program.